How to Treat Hepatocellular Carcinoma in Elderly Patients - Piera Federico; Emilio Francesco Giunta; Annalisa Pappalardo; Andrea Tufo; Gianpaolo Marte; Laura Attademo; Antonietta Fabbrocini; Angelica Petrillo; Bruno Daniele (MDPI AG, 2021)
Hepatocellular carcinoma (HCC) is the primary tumour of the liver with the greatest incidence, particularly in the elderly. Additionally, improvements in the treatments for chronic liver diseases have increased the number of elderly patients who might be affected by HCC. Little evidence exists regarding HCC in old patients, and the elderly are still underrepresented and undertreated in clinical trials. In fact, this population represents a complex subgroup of patients who are hard to manage, especially due to the presence of multiple comorbidities. Therefore, the choice of treatment is mainly decided by the physician in the clinical practice, who often tend not to treat elderly patients in order to avoid the possibility of adverse events, which may alter their unstable equilibrium. In this context, the clarification of the optimal treatment strategy for elderly patients affected by HCC has become an urgent necessity. The aim of this review is to provide an overview of the available data regarding the treatment of HCC in elderly patients, starting from the definition of "elderly" and the geriatric assessment and scales. We explain the possible treatment choices according to the Barcelona Clinic Liver Cancer (BCLC) scale and their feasibility in the elderly population.